(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Hemorrhoidal disease, a prevalent benign anorectal disorder, has a substantial influence on patients’ quality of life and entails significant health and financial strains. The focus of this study is to evaluate the therapeutic value of Siddha medicine, Thantrikai Choornam, in alleviating first-degree internal hemorrhoids (Raththa Moolam). Method: A descriptive case series was carried out at the Government Siddha Medical College & Hospital in Palayamkottai, involving 20 patients (80% male, mean age 45.94±2.60 years) reported having bleeding hemorrhoids. Participants were prescribed Thantrikai Choornam (2 g, twice daily) for 24 days. Clinical symptoms such as bleeding, discomfort, constipation, and other parameters were graded both before and after treatment. Results: Substantial improvements were observed following treatment, with 75% of patients observing an overall decrease in bleeding severity from grade 3 to 0, along with a resolution of anal pain. Constipation alleviated for 85% of individuals. The average hemoglobin level raised from 11.88 to 12.25 g/dL. The statistical analysis demonstrated noteworthy reductions in the majority of complaints (p < 0.05). Conclusion: This case series illustrates that Thantrikai Choornam delivers a beneficial intervention for first-degree hemorrhoids, with considerable improvements in primary symptoms. The outcomes offer a call to further investigations into Siddha medicines role in contemporary therapeutic practices for managing hemorrhoidal disease.